THE PROBLEM OF EQUILIBRIUM IN THE PANJI STORY: A TZVETAN TODOROV’S NARRATOLOGY PERSPECTIVE - Taum, Yoseph Yapi (International Journal of Humanity Studies (IJHS), 2018)
Narrative is understood as the record of human activities which relate strongly to a cultural matrix.  Narrative, in terms of story or story telling, is representative of factual and fictional achievement placed in a chronological or causal order. Therefore, narrative and narratology have an important function in understanding cultural activities. Some structuralist scholars, especialy those living during 1960-1980, created a special theory on narratology. There are four specialists of narratology; they are: Vladimir Propp, Claude Levi-Strauss, Tvsetan Todorov, and A. J. Greimas. They claimed the same perspective, that all narrative (such as folktale, myth, and legend) in fact share the same fundamental structure (i.e grammar, syntactical structure, semantics axes, actantial structure, or logical structure). Panji Story is one of Indonesian heritage stories popular during the rule of Madjapahit Kingdom. The narratives were transmitted into folktales, oral literature, written literature, hikayat, or engraved as the reliefs at ancient temples. The narrative which was originated from Singasari Kingdom was so pervasive in East Javanese culture, as it created a Panji Culture (Nurcahyo, 2016). The spread of the narratives was so extensive, reaching Bali, Nusa Tenggara, Sumatra, Borneo, Papua, and to neighbouring countries such as Malaysia, Thailand, Cambodia, Laos, and Myanmar. This paper aims at revealing narrative sequences of Panji Narratives in line with Todorov’s narrative theory, especially in relation to his narratology theory of equilibrium. Todorov’s equilibrium gets a new perspective and meaning.DOI: https://doi.org/10.24071/ijhs.2018.020110